The Makeup of Self-Expression: A Study on The Impact of Self-Congruence on Purchase Intentions With Brand Experience Mediation Among Makeup Artist Consumers - Dana Aditya; Matheous Tamonsang (CV. Syntax Corporation Indonesia, 2023)
A makeup artist (MUA) is a type of business that aims to enhance an individual's appearance through the use of cosmetic materials and tools. The term